Faktor-faktor yang Mempengaruhi Penggunaan Rokok Elektrik di Kalangan Komunitas Vape Muda - Banowo, Agus Sri; Fauziyah, Nazhifa; Krisdianto, Boby Febri (Jurnal Ners, 2025)
The increase in e-cigarette users in society continues to grow, which can endanger bodily health. This study aims to determine the factors associated with e-cigarette users in the "Vape Gaming Store" association in the GOR H. Agus Salim area in Padang City. This research method is quantitative research. The research design is an analytic correlation with a cross-sectional approach. The sample in this study amounted to 50 people, with sampling techniques using total sampling. The results of the study were analyzed using the chi-square test. Based on the results of the chi-square test, there is a relationship between friend factors, knowledge factors, social media factors, and lifestyle factors, with a p-value <0.05. In this study, the social media factor is highly influential, increasing the likelihood of e-cigarette use by 9000 times. This factor can be utilized to help disseminate information and educate through social media by giving warnings about the long-term dangers of e-cigarettes in marketing content or photos.